Police Efforts in the Reduction of Fear of Crime in Local Communities – Big Expectations and Questionable Effects - Meško, Gorazd; Fallshore, Marte; Rep, Mojca; Huisman, Aletha (Sociologija. Mintis ir veiksmas, 2007)
Making police officers approachable and visible is one of the most important factors in reducing fear of crime. However, the public also requires their effectiveness in crime fighting. Community policing relies on factors such as approachability and visibility of the police, but does not offer solutions for factors like neighbourhood decay. The role of police in the reduction of fear of crime is quite paradoxical – on the one hand their presence in neighbourhoods reassure citizens, while on the other hand their presence can be understood as a response to more crime and disorder.